Norms and Standards for Capacity of Airport Terminals - Planning Commission (Planning Commission, 2009)
India has been witness to an unprecedented rise in air travel, both domestic and international. This has been an outcome of the policy of liberalisation in air travel in the context of the robust growth of the Indian economy. However, the infrastructure at several airports would need to be augmented to keep pace with the rapid increase in air travel. An ambitious plan for the development of airports was, therefore, approved by the Committee on Infrastructure and is presently under implementation. While the four metro airports at Delhi, Mumbai. Bangalore and Hyderabad are being developed and operated through Public Private Partnership, the airports at Kolkata and Chennai as well as at 35 non-metro airports are being redeveloped and modernised by the Airports Authority of India (AAI), the statutory authority responsible for developing and operating airports under the provisions of the Airport Authority of India Act, 1994.
Planning Commission Government of India
Planning Commission Government of India